The impact of COVID-19 on the wellbeing of the UK nursing and midwifery workforce during the first pandemic wave: A longitudinal survey study. (March 2022) - Couper, Keith; Murrells, Trevor; Sanders, Julie; Anderson, Janet E.; Blake, Holly; Kelly, Daniel; Kent, Bridie; Maben, Jill; Rafferty, Anne Marie; Taylor, Rachel M.; Harris, Ruth
Abstract: Background: The specific challenges experienced by the nursing and midwifery workforce in previous pandemics have exacerbated pre-existing professional and personal challenges, and triggered new issues. We aimed to determine the psychological impact of the COVID-19 pandemic on the UK nursing and midwifery workforce and identify potential factors associated with signs of post-traumatic stress disorder. Methods: A United Kingdom national online survey was conducted at three time-points during the first wave of the COVID-19 pandemic between April and August 2020 ( T1 and T2 during initial wave; T3 at three-months following the first wave). All members of the UK registered and unregistered nursing and midwifery workforce were eligible to participate. The survey was promoted via social media and through organisational email and newsletters. The primary outcome was an Impact of Events Scale-Revised score indicative of a post-traumatic stress disorder diagnosis (defined using the cut-off score ≥33). Multivariable logistic regression modelling was used to assess the association between explanatory variables and post-traumatic stress disorder. Results: We received 7840 eligible responses ( T1 - 2040; T2 - 3638; T3 - 2162). Overall, 91.6% participants were female, 77.2% were adult registered nurses, and 28.7% were redeployed during the pandemic. An Impact of Events Scale-Revised score ≥33 (probable post-traumatic stress disorder) was observed in 44.6%, 37.1%, and 29.3% participants at T1, T2, and T3 respectively. At all three time-points, both personal and workplace factors were associated with probable post-traumatic stress disorder, although some specific associations changed over the course of the pandemic. Increased age was associated with reduced probable post-traumatic stress disorder at T1 and T2 (e.g. 41–50 years at T1 odds ratio (OR) 0.60, 95% confidence interval (CI) 0.42–0.86), but not at T3 . Similarly, redeployment with inadequate/ no training was associated with increased probable post-traumatic stress disorder at T1 and T2, but not at T3 (T1 OR 1.37, 95% CI 1.06–1.77; T3 OR 1.17, 95% CI 0.89–1.55). A lack of confidence in infection prevention and control training was associated with increased probable post-traumatic stress disorder at all three time-points (e.g. T1 OR 1.48, 95% CI 1.11–1.97). Conclusion: A negative psychological impact was evident 3-months following the first wave of the pandemic. Both personal and workplace are associated with adverse psychological effects linked to the COVID-19 pandemic. These findings will inform how healthcare organisations should respond to staff wellbeing needs both during the current pandemic, and in planning for future pandemics.